2008
DOI: 10.1603/0046-225x-37.6.1508
|View full text |Cite
|
Sign up to set email alerts
|

Influence of <I>Prunus</I> spp., Peach Cultivars, and Bark Damage on Oviposition Choices by the Lesser Peachtree Borer (Lepidoptera: Sesiidae)

Abstract: An examination of oviposition choices by the lesser peachtree borer, Synanthedon pictipes (Grote and Robinson) (Lepidoptera: Sesiidae), showed that wounded peach, Prunus persica (L.) Batsch, bark was attractive to females for oviposition. Females responded to bark that was injured mechanically (e.g., hammer blows, knife cuts, pruning wounds), infested by lesser peachtree borer larvae or injured by disease. In fact, there was no difference in female oviposition response to knife cut wounds and knife cut wounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Because eggs were afÞxed to cups and substrates by a thin, glue-like secretion and easily damaged by attempts to remove them, they were left in place until hatch when neonates could easily be transferred. In contrast, oviposition by S. pictipes in the laboratory occurs within 2Ð3 h after mating (Reed and Tromley 1985), and eggs can easily be collected by gently tapping substrates over a piece of waxed paper (Cottrell et al 2008). Although dogwood borer females deposited signiÞcantly more eggs on apple substrates wrapped in cheesecloth, the variability in daily and total oviposition among females was high, and accurate assessments of the rate of oviposition await the results of ongoing studies of the stimuli that trigger egg deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Because eggs were afÞxed to cups and substrates by a thin, glue-like secretion and easily damaged by attempts to remove them, they were left in place until hatch when neonates could easily be transferred. In contrast, oviposition by S. pictipes in the laboratory occurs within 2Ð3 h after mating (Reed and Tromley 1985), and eggs can easily be collected by gently tapping substrates over a piece of waxed paper (Cottrell et al 2008). Although dogwood borer females deposited signiÞcantly more eggs on apple substrates wrapped in cheesecloth, the variability in daily and total oviposition among females was high, and accurate assessments of the rate of oviposition await the results of ongoing studies of the stimuli that trigger egg deposition.…”
Section: Discussionmentioning
confidence: 99%
“…This is indicative of the ability of these fungal species to compromise the health and possibly reduce the longevity of peach trees, in addition to other existing issues that already compromise peach tree health including PTSL and ARR (Beckman et al 1998;Ritchie and Clayton 1981;Cottrell et al 2008). More research is needed to confirm these observations, and to understand the epidemiology of these organisms in peach, including the fungal distribution within trees, the process of infection and/or colonization (including the effect of single and multiple infections), the effect of tree and limb age, disease severity on different germplasm, and the effect of colonization on tree limb strength.…”
Section: Identity Of the Main Fungi Colonizing Peach Woodmentioning
confidence: 99%
“…Wounds caused by pruning, and bark damage caused by other orchard operations on peach trees may allow for infestation by certain insects (Cottrell et al 2008), and various fungi are reported to grow in these wounds (Doepel et al 1979;Adaskaveg et al 1993). Furthermore, prevailing weather appears to affect incidence of colonization of wounds (Doepel et al 1979;Adaskaveg et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…A common, native host plant is black cherry, Prunus serotina Ehrh., whereas examples of exotic hosts also include peach; sour cherry, Prunus cerasus L.; and European plum, Prunus domestica L. (Girault 1907, Vogel andNeiswander 1933). This multivoltine pest damages host plants through larvae feeding on the cambium of the trunk and structural scaffold limbs; pupation follows at these feeding sites (Johnson et al 2005a, Cottrell et al 2008.…”
mentioning
confidence: 99%